О ПРАВОВОЙ ПРИРОДЕ ДОГОВОРА НАЙМА-ПРОДАЖИ И ДОГОВОРА АРЕНДЫ С ПРАВОМ ВЫКУПА (НА ПРИМЕРЕ ЗАКОНОДАТЕЛЬСТВА РЕСПУБЛИКИ БЕЛАРУСЬ И УКРАИНЫ) - Вартанян, А. М. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2016)
The article considers the issues of determining the legal nature of the contract of sale and contract of lease with option to purchase. Substantiates the hybrid nature of these contracts. The author analyzes the current legislation of the Republic of Belarus and Ukraine, regulating relations for hire, sale & rent with option to buy. Indicates the similarity of legal regulation of these relations in the Republic of Belarus and Ukraine. The conclusion about the need to expand the circle of relations to which the application of rules on hiring and selling.